Modular Branched Neurotensin Peptides for Tumor Target Tracing and Receptor-Mediated Therapy: A Proof-of-Concept - Falciani, C.; Lelli, B.; Brunetti, J.; Pileri, S.; Cappelli, A.; Pini, A.; Pagliuca, C.; Ravenni, N.; Bencini, L.; Menichetti, S.; Moretti, R.; De Prizio, M.; et al. (Current Cancer Drug Targets, 2010)
The aim of this study was to demonstrate that oligo-branched peptides can be effective either for spotlighting tumor cells that overexpress peptide receptors, or for killing them, simply by exchanging the functional moiety coupled to the conserved receptor-targeting core. Tetra-branched peptides containing neurotensin (NT) sequence are described here as selective targeting agents for human colon, pancreas and prostate cancer. Fluorophore-conjugated peptides were used to measure tumor versus healthy tissue binding in human surgical samples, resulting in validation of neurotensin receptors as highly promising tumor-biomarkers. Drug-armed branched peptides were synthesized with different conjugation methods, resulting in uncleavable adducts or drug-releasing molecules. Cytotoxicity on human cell lines from colon (HT-29), pancreas (PANC-1) or prostate (PC-3) carcinoma indicated branched NT conjugated with MTX and 5-FdU as the most active agents on PANC-1 (EC50 4.4e-007 M) and HT-29 (1.1e-007 M), respectively. Tetra-branched NT armed with 5-FdU was used for in vivo experiments in HT-29-xenografted mice and produced a 50% reduction in tumor growth with respect to animals treated with the free drug. An unrelated branched peptide carrying the same drug was completely ineffective. In vitro and in vivo results indicated that branched peptides are valuable tools for tumor selective targeting.
Keywords: (PANC-1)